2015
DOI: 10.3109/03008207.2015.1045139
|View full text |Cite
|
Sign up to set email alerts
|

Antlerogenic stem cells: molecular features and potential in rabbit bone regeneration

Abstract: Our findings indicate that the use of both antlerogenic stem cell implants and the preparations derived from the cells offer alternative approaches to those based on autologous stem cells in the biological stimulation of osteogenesis and in bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…CD9, an ESC marker, was defined as a surface marker of the AS cells in the previous studies 6,41 . We also detected its expression in all three types of AS cells in this study (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD9, an ESC marker, was defined as a surface marker of the AS cells in the previous studies 6,41 . We also detected its expression in all three types of AS cells in this study (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on a canine model using a purified form of the ASC homogenate showed a significant improvement in the biophysical properties of the skin in the healing regions; moreover, in experimental group there was significantly better hydration of the stratum corneum than in placebo group (glycerol and PBS solution) or in group without any treatment [ 26 ]. In rabbits, MIC-1 cells were used to regenerate auricular cartilage [ 33 ] and bone tissue [ 27 ]. All of the above-mentioned application studies, regardless of the route of administration, did not show any side effects or cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Revitacell contains stem cells homogenate derived from the deer antler stem cell line MIC-1 (listed in CosIng Cosmetic Ingredient Database as: “Deer antler cell extract”) [ 25 ]. Full characteristic of MIC-1 cell line is described by Cegielski et al and Dąbrowska et al [ 25 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…CD9 is a cell surface marker and expresses in ASCs. 9,16 The lineage fidelity of the established ASCs lines was monitored using marker CD9 via flow cytometry, which is described elsewhere. 17 Briefly, the primary cultured APCs, PPCs, and RMCs were incubated, respectively, with 5% goat serum to block nonspecific staining for 30 min, then with anti-CD9 antibody (LS-C46004; LifeSpan, USA) for 1 hr at 4C after wash with cold phosphate-buffered saline (PBS).…”
Section: Flow Cytometrymentioning
confidence: 99%